“The Cordyceps spider”: Taczanowskia waska sp. nov. (Araneae: Araneidae), a new spider species and a novel case of mimicry of an araneopathogenic fungus (Cordycipitaceae: Gibellula) - Díaz-Guevara, David R.; Bentley, Alexander Griffin; Dupérré, Nadine (Zootaxa, 2026)
Herein, we describe a new species of the rare spider genus Taczanowskia Keyserling, 1879 (Araneae: Araneidae), Taczanowskia waska sp. nov. (♀) from the Ecuadorian Amazon. Additionally, we discuss its unique fungal mimicry, comment on Taczanowskia ecology, and provide an updated taxonomic key for females of the genus. The importance of this discovery extends well beyond the description of a novel taxon, representing the first reported case of Arachnid mimicry of an araneopathogenic fungus. Finally, we discuss the application of citizen science to collecting ecological and biogeographical data on arachnids and its potential use for describing new taxa.